Stulicent Cafe / Sameson Ampias ... [et al.] - Ampias, Sameson; Abdullah, Mohd Roze; Eram, Mustaqim; Lamjad, Hafizah; Rasnin, Rasyidah; Bustam, Nur Ezzati (2014)
The business oriented cafe in our country is getting wider and became a something that very popular in Kota Kinabalu especially among students. Because of that, our company wants to venture in this kind of business which is cafe with many enhancements that can attract more customers. The name of our company is STULfCENT CAFE which in fuJJ name is Student Life Centre. We purposely choose Student Life as our business name because we want to show something that interesting that combined our cafe with many services we provided such as Information Communication and Technology (ICT), foods and drinks, drive thru, food and de! ivery services. Our cafe is not only for interaction social and communication, but also act as a place that gives student comfortable place for any discussion. When student comes to surfing internet, they also can order any junk foods and drinks and we will serve for them. The inspiration to establish this cafe is come up with our own ideas when we still a student. We want to make something different with other cafe which only focus on selling foods and drinks because it is commonly provided by other cafe. Some students want something differeJ1t that more attract full to release their stress. So, to make our business different with other cyber cafe concept m ota Kinabalu Sabah, we are providing a variety of products. The market for this business is also doing well in Kota Kinabalu, Sabah because the population is increasing from time to time and can fulfil the student preferences and demand as well. Our location will be situated StuLiCent Co. located in Sulaman Sentral, Kuala Menggatal, Sabah, the new developed area which is a strategic place for us to start and to build further our business. Furthermore, it gives us advantages to establish our business here because there are no cafe open that provides food and plus printing and photocopy. It was very suitable for our customers because the place was strategic and located at the middle from urban to Kota Kinabalu. It is also has good economic development and there are lots of parking spaces. The shop that we have selected can be easily seen from the main road which is advantage for our business to be known. The market target for our business will be particularly for students, lecturer and other people as well. Our target Gustomers are people around Sabah but we will look for opportunity to open other branches in peninsular Malaysia.